Nutrition knowledge among Malaysian elderly - Norimah A.Karim,; Nik Shanita Safii,; Safiah Mohd Yusof,; Norazliana Mohd Noor,; Zawiah Ahmad,; Tee, E Siong (Penerbit UKM, 2008)
This paper reports the nutrition knowledge of Malaysian elderly, as part of a nationwide study to evaluate the status of nutrition knowledge, attitude and practice (KAP) of food and nutrition among various communities in Malaysia. A total of 906 elderly, age ranging between 60 to 96 years old, with mean age 67.4 ± 6.7 years representing all states in Malaysia participated in the study. An interview administered questionnaire was used to assess the nutrition knowledge and to collect demographic data of the elderly. Subjects were in the 60-65 years (51%) and more than 65 years (49%) age category. There were 46% Malays, 32% Chinese, 6% Indians while the remaining 16% comprised of other minority groups in Malaysia such as Iban, Kadazan, Melanau, Orang Asli and others. More than half of the elderly (54%) had no formal education,36% completed primary schooling and only 9% finished secondary education. Overall 73% elderly were categorized as having poor nutrition knowledge, 18% moderate and only 9% good. The minority groups had the highest percentage of poor nutrition knowledge (91%) while the Chinese had thehighest percentage of good nutrition knowledge (11%). More female (78%) than male (67%) had poor nutrition knowledge, in contrast to more male(10%) than female (8%) with good nutrition knowledge. Chi square test showed that there was a significant correlation between educational status and nutrition knowledge. This was reflected in the results which showed that 81% elderly with no formal education were categorized in the poor nutrition knowledge group. Majority of the elderly did not know about foods to be consumed most (88%), or to be eaten least (87%). Only a quarter to a third of the elderly responded correctly to questions on nutrient function and content. The question on foods with high salt was well responded by the elderly (65%). It is quite discouraging to show that a majority of Malaysian elderly had poor nutrition knowledge. This study indicated that appropriate nutrition education interventions need to be implemented to improve the shortcomings of nutrition knowledge among the Malaysian elderly.